2019
DOI: 10.1247/csf.19033
|View full text |Cite
|
Sign up to set email alerts
|

Localization of BCR-ABL to Stress Granules Contributes to Its Oncogenic Function

Abstract: The oncogenic tyrosine kinase BCR-ABL activates a variety of signaling pathways and plays a causative role in the pathogenesis of chronic myelogenous leukemia (CML); however, the subcellular distribution of this chimeric protein remains controversial. Here, we report that BCR-ABL is localized to stress granules and that its granular localization contributes to BCR-ABL-dependent leukemogenesis. BCR-ABL-positive granules were not colocalized with any markers for membrane-bound organelles but were colocalized wit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…The percentage of various studies is shown in Figure 2. Meanwhile, the majority of studies, about 66% of studies, are dedicated to cell culture studies only (Baguet et al, 2007;Miyoshi et al, 2007;Arimoto et al, 2008;Eisinger-Mathason et al, 2008;Goulet et al, 2008;Bus脿 et al, 2010;Gottschald et al, 2010;Guo et al, 2010;Kalra et al, 2010;Nikpour et al, 2011;Taniuchi et al, 2011aTaniuchi et al, ,b, 2014Park et al, 2012;Fournier et al, 2013;Pizzo et al, 2013;Thedieck et al, 2013;Chang et al, 2014;Kano et al, 2014;Podszywalow-Bartnicka et al, 2014;Yuan et al, 2014;Liu et al, 2015;Somasekharan et al, 2015;Szafron et al, 2015;Valentin-Vega et al, 2016;Weeks et al, 2016;Narayanan et al, 2017;Wall and Lewis, 2017;Takayama et al, 2018;Haghandish et al, 2019;Heberle et al, 2019;Kashiwagi et al, 2019;Mazloomian et al, 2019;Cui et al, 2020;Do et al, 2020;Brown et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The percentage of various studies is shown in Figure 2. Meanwhile, the majority of studies, about 66% of studies, are dedicated to cell culture studies only (Baguet et al, 2007;Miyoshi et al, 2007;Arimoto et al, 2008;Eisinger-Mathason et al, 2008;Goulet et al, 2008;Bus脿 et al, 2010;Gottschald et al, 2010;Guo et al, 2010;Kalra et al, 2010;Nikpour et al, 2011;Taniuchi et al, 2011aTaniuchi et al, ,b, 2014Park et al, 2012;Fournier et al, 2013;Pizzo et al, 2013;Thedieck et al, 2013;Chang et al, 2014;Kano et al, 2014;Podszywalow-Bartnicka et al, 2014;Yuan et al, 2014;Liu et al, 2015;Somasekharan et al, 2015;Szafron et al, 2015;Valentin-Vega et al, 2016;Weeks et al, 2016;Narayanan et al, 2017;Wall and Lewis, 2017;Takayama et al, 2018;Haghandish et al, 2019;Heberle et al, 2019;Kashiwagi et al, 2019;Mazloomian et al, 2019;Cui et al, 2020;Do et al, 2020;Brown et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…HuR influenced BRCA1 translation and mRNA stability positively (Podszywalow-Bartnicka et al, 2014). It should be noted that the oncogenic tyrosine kinase BCR-ABL is also localized in the structure of SGs, and the formation of granular structure is necessary for the activity of ABL kinase and N-terminal region of BCR (Kashiwagi et al, 2019).…”
Section: Proliferationmentioning
confidence: 99%
“…ABL is another famous tyrosine kinase that has DNA-binding activity and is involved in apoptosis and DNA damage repair; CML could be resulted due to the juxtaposition of ABL to BCR protein [48] . The fusion proteins are characterized as having liquid-like properties, while the ABL kinase activity is necessary for promoting oncogenesis [49] . The fusion proteins activate pathways involved in cell proliferation, adhesion, differentiation, and cell survival [48] , and promote the enrichment of stress granules [49] .…”
Section: Global Translational Medicinementioning
confidence: 99%
“…The fusion proteins are characterized as having liquid-like properties, while the ABL kinase activity is necessary for promoting oncogenesis [49] . The fusion proteins activate pathways involved in cell proliferation, adhesion, differentiation, and cell survival [48] , and promote the enrichment of stress granules [49] . It is believed that the fusion protein alters the properties and composition of stress granules.…”
Section: Global Translational Medicinementioning
confidence: 99%
“…Fluorescence imaging and data analysis were performed essentially as described previously (Fujioka et al, 2019;Kashiwagi et al, 2019b). In brief, cells transfected with mCherry-CoV-S or mCherry-CoV-2-S vectors were stained with Hoechst 33342 for 15 min and placed in a stage-top incubation chamber maintained at 37掳C on a Nikon Ti2 microscope (Nikon, Tokyo, Japan) equipped with a Zyla5.5 scientific complementary metal oxide semiconductor camera (Oxford Instruments, Belfast, UK).…”
Section: Fluorescence Microscopymentioning
confidence: 99%